PROFESIONALISME GURU MATEMATIKA DALAM MERENCANAKAN PEMBELAJARAN BERBASIS KOMPETENSI - SUPARNI SUPARNI (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2016)
Good Lesson Planning will make teachers easier in helping students’ learning; and students are also assisted in understanding the subject matter. Lesson Plan is developed according to the needs and characteristics of learners, schools and subjects. Each teacher is required to formulate a complete syllabus and lesson plans. A math teacher should be able to design a lesson plan in accordance with the characteristics and approaches contained in math. This study aimed to determine how the knowledge and ability of math teachers of Senior High Schools in Padangsidimpuan city in developing lesson planning. This research is classified into descriptive study. Data were collected by using competency test and questionnaires. Based on data analysis, it can be concluded that the teachers’ knowledge in developing Lesson Plans is enough, while the ability of the teachers in developing is good enough. Finally, it is known that there is the significant correlation between teachers’ knowledge and teachers’ ability in developing Lesson Plans.